ANALISIS EVALUASI IMPLEMENTASI SIK 5NG PADA BIDAN DESA DENGAN METODE TAM DI WILAYAH KERJA DINAS KESEHATAN KABUPATEN DEMAK TAHUN 2016 - Ayu Laraswaty Lumban Gaol; Atik Mawarni; Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2017)
Central Java Provincial Health Office has developed Health Information System that is SIK 5NG “Jateng Gayeng Nginceng Wong Meteng” which is designed for pregnant recording and reporting system can be done in realtime so as to provide accurate, relevant, and timely data and information for the decision-making procces. One of the districts that have utilized SIK 5NG is Demak Regency, but not yet maximally utilized by its users, Village Midwives. The SIK 5NG development phase requires an evaluation for the improvement of further development. The purpose of this research is to analyze the evaluation of SIK 5NG implementation in the working area of Demak District Health Office by TAM method (Technology Acceptance Model) which viewed from perceived ease of use, perceived usefulness, attitude toward using, behavioral intention of use, and actual system usage. This research uses quantitative and qualitative approach. The population of this research is 281 Village Midwives who work in the working area of Demak District Health Office. The sample of this research is 38 Village Midwives. Sampling technique using Simple Random Sampling technique. The results show that there are still some deficiencies in each variable, such as the village midwife is not easy to use SIK 5NG in recording and reporting of pregnant women, not using SIK 5NG to calculate indicator on KIA program, and not using SIK 5NG to produce information about women pregnant. One of the reasons presented is the frequent server interruption so the system is difficult to access. Therefore, it is advisable for the midwife coordinator to evaluate and monitor the village midwife in utilizing the SIK 5NG from entrering data, calculating indicator on KIA program to produce information about pregnant women.